When Should International Courts Intervene? How Populism, Democratic Decay and Crisis of Liberal Internationalism Complicate Things. (21st January 2022) - Petrov, Jan
Abstract: Shai Dothan's book International Judicial Review aims to refute criticism which stresses international courts' (ICs) lack of legitimacy, epistemic inferiority, suffocation of public deliberation, susceptibility to capture and production of bad outcomes. This essay argues, however, that there is an important line of criticism of ICs stemming from a profounder disagreement with the post-Cold War international legal system – the critique related to ethno-national and/or authoritarian populism – which poses novel challenges to justifying ICs. Engaging with Dothan's arguments through the prism of the populist backlash, this essay contributes to recent scholarship on populism and international law by explaining how populism challenges the justification of IC interventions. Populists treat majority will and national/regional identity as the exclusive sources of the common good, and this casts doubts on arguments favouring multilateralism, such as the Condorcet Jury Theorem used by Dothan. It also allows populists to re-frame IC interventions as threats to people's well-being and disseminate 'counter-myths' delegitimizing ICs, which may impair ICs' ability to produce good outcomes. Altogether, populism has the capacity to increase the costs of international judicial intervention for ICs and reduce the costs of non-compliance and exit for the populists, which confronts IC scholars and judges with new challenges.